Simultaneous removal of carbon dioxide, sulphur dioxide and nitrogen oxides using activated carbon modified with metal oxides - Madzaki, Hazimah (2018)
Greenhouse gases act as a blanket to keep the Earth warm. However, excessive release of greenhouse gases in the atmosphere causes the Earth’s temperature to rise above the threshold that led to many environmental problems. Carbon dioxide (CO2) is the largest contributor to this problem, but other gases make a significant contribution. Malaysia’s greenhouse gas emissions are mainly from power station industry that produces electricity through burning of fossil fuels. Coal-fired power plants emit high concentration of CO2 as well as sulphur dioxide (SO2) and oxides of nitrogen (NOx), two of the most widespread and dangerous gases other than CO2. These coal-fired power plants used many technologies to remove these gases from the flue gas stream. However, the technologies used are different for each gases; carbon capture and storage for CO2 and flue gas desulphurization for SO2 and low- NOx burner for NOx control. This multistage and complex removal processes can be very expensive due to high capital and operating cost. Hence, it is important to integrate the multistage process into a single step process for simultaneous removal of CO2, SO2 and NOx to reduce the time and cost for flue gas cleaning. This paper presents a simple way of modification of activated carbon surface using hydrothermal treatment and impregnation with metal oxides. The CO2 adsorption performance of the modified activated carbon is evaluated by using a CO2 adsorption unit while the simultaneous adsorption of CO2, SO2 and NOx was done using flue gas adsorber unit with actual flue gas stream from combustion of coal in electrical furnace. Two types of metal oxides are used in this study which are cerium oxide (CeO2) and copper oxide (CuO). The adsorption study consists of activated carbon hydrothermally treated with metal oxides (ACCe-HT, ACCu-HT and ACCeCu-HT) and also activated carbon impregnated with metal oxides (ACCe-WI, ACCu-WI and ACCeCu-WI). The objectives of the research are to investigate the physical-chemical properties of modified activated carbon with various metal oxides and to investigate the adsorption capacity in simultaneous removal of carbon dioxide, sulphur dioxides and nitrogen oxides. In this study, the performance of activated carbon modified by hydrothermal treatment and impregnation techniques was compared. The prepared samples were characterized by different techniques using Brunauer-Emmet-Teller (BET) surface area analysis, Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD). From BET analysis, the surface area and pore volume of raw AC was 1,288 m2/g and 0.38 cm3/g respectively. After modification, these values decreased with ACCe-HT having the highest surface area among the other modified sample which was 1,169 m2/g. This result corresponds to the SEM images that the surface of ACs were covered with metal oxides and peaks of metal oxides appear in XRD spectrum. The adsorption of CO2 was investigated using a CO2 adsorption unit, whereby 10% of CO2 gas was passed through the samples until a breakthrough point was achieved. In the adsorption study, it was found that ACCe-HT had the highest adsorption capacity of 0.86 mmol/g with a breakthrough time of 19.33 min while ACCe-WI, ACCu-WI, ACCeCu-WI, ACCu-HT and ACCeCu-HT had the adsorption capacity of 0.12, 0.52, 0.06, 0.59 and 0.56 mmol/g respectively. In isotherm study using three isotherm models; Freundlich, Sips and Toth, it was also found that Toth Isotherm model shows good fit to the experimental data with correlation coefficient of 0.9910. In simultaneous adsorption from flue gas study using hydrothermal treated samples the adsorption capacity for ACCe-HT, ACCu-HT and ACCeCu-HT were 3.61, 1.16 and 0.50 mmol/g for CO2, 0.43, 0.57 and 0.31 mmol/g for SO2 and 0.82, 0.96 and 0.78 mmol/g for NOx. Overall, all objectives have been satisfied and it can be said that hydrothermally treated AC with CeO2 has the potential to be used as adsorbent for CO2 capture as well as SO2 and NOx and the ability is comparable to the carbon monolith. Therefore, it is suitable to be applied in industry particularly flue gas system for CO2, SO2 and NOx adsorption.